Budidaya Lele di Lahan Sempit Kalurahan Caturtunggal ber-basis Pakan Alternatif pada Era Pandemi Covid-19 - Nur Indah Septriani; Wahyu Aristyaning Putri; Fajar Sofyantoro; Dwi Sendi Priyono (STMIK Royal, 2022)
The era of the Covid-19 pandemic, causing many people who are affected by work stoppages or decreased income so that nutritious food needs are less fulfilled. This requires the people of Caturtunggal Urban Village to conduct food self-sufficiency, one of which is by utilizing the yard for the cultivation of catfish budikdamber method based on the development of alternative feed. From this program, people of Caturtunggal Urban Village can use the narrow land of their homes for catfish cultivation to realize food security, as well as provide alternative solutions for the development of cheap, quality, and environmentally friendly feed. Based on the results of the evaluation, the community stated that the use of alternative feed is very useful to maintain the quality of aquaculture and reduce mortality, although there is a lack of catfish growth and a lower appetite than catfish fed. In the future, there need to be further studies on the composition of alternative feed that is environmentally friendly and increases the growth of catfish quickly. This program is a prefix program that is planned to run for at least 5 years with the final target of making UMKM for catfish cultivation and catfish processed products. So that, there needs to be a sustainability program conducted between the community, the village government, and the academic community.